Redefining Diversity: Political Responses to the Post-PICS Environment - Siegel-Hawley, Genevieve; Frankenberg, Erica (Peabody journal of education, 2011)
This article examines the federal and local political response to the Parents Involved decision. At the federal level, developments suggest a reaction to Parents Involved that, since President Obama has taken office, has been largely supportive of voluntary efforts to promote racial diversity. The administration has also been seeking to enforce more traditional race-based civil rights cases. Locally, even though reactions to the decision are as varied as the districts themselves, three broad categories of political responses emerge from our review of post—Parents Involved student assignment policies. They are the adoption of multifactor student assignment plans, the adoption of class-based (e.g., race-neutral) student assignments, and the elimination of efforts to pursue diversity. This article is particularly interested in examining the first two categories of responses. In doing so, we argue that some school districts are pursuing a redefined conceptualization of diversity in a challenging legal and political climate.